2014
DOI: 10.1093/jscr/rju071
|View full text |Cite
|
Sign up to set email alerts
|

A case of CD68 negative histiocytic sarcoma of axilla masquerading as metastatic breast cancer

Abstract: Histiocytic sarcoma is a malignant proliferation of cells showing morphological and immunophenotypic features of mature tissue histiocytes. Most of the cases in the literature have reported CD68 positivity. We report a case of histiocytic sarcoma whose presentation mimicked a metastatic breast cancer. A 40-year-female patient presented with a 13 × 11 cm left axillary mass in close proximity to the left breast. Tru-cut biopsy from the lesion suggested the diagnosis of a lymphoid neoplasm. Complete excision of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…However, S100 is positive in approximately 33% of HS, therefore, a positive S100 does not rule out HS,. [ 9 ] In our case, pan-CK, EMA, GFAP, olig2 were negative but CD45 was positive, suggesting a lymphohematopoietic cell lineage.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…However, S100 is positive in approximately 33% of HS, therefore, a positive S100 does not rule out HS,. [ 9 ] In our case, pan-CK, EMA, GFAP, olig2 were negative but CD45 was positive, suggesting a lymphohematopoietic cell lineage.…”
Section: Discussionmentioning
confidence: 59%
“…3 ). [ 1 9 , 11 32 ] Brown et al reported the longest survival at greater than 60 months. The most common treatment reported was a combination of surgery, radiotherapy and chemotherapy (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Histiocytic sarcoma is known to occur in various organs; however, its association with the breast has rarely been reported. There have been a few reported case studies of histiocytic sarcoma invasions into the breast; however, the reported primary sites of the tumor in these case studies were the soft tissue of axilla and the subcutaneous breast tissue [27]. To the best of our knowledge, this case study is the first report of primary histiocytic sarcoma of the breast parenchyma.…”
Section: Discussionmentioning
confidence: 96%
“…Connective tissue, respiratory system, and central nervous system are among the other areas that may be impacted [10]. After conducting a thorough search of the existing literature, it was discovered that only three previous instances of primary breast HS involvement have been documented [11][12][13] (Table 1). Histopathology examination with the aid of immunohistochemistry is essential to confirm the diagnosis due to the lack of specificity in radiology studies.…”
Section: Discussionmentioning
confidence: 99%
“…Connective tissue, respiratory system, and central nervous system are among the other areas that may be impacted [ 10 ]. After conducting a thorough search of the existing literature, it was discovered that only three previous instances of primary breast HS involvement have been documented [ 11 - 13 ] (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%